GAMBARAN PELAKSANAAN PEMBELAJARAN KURSUS MENJAHIT DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) AS-SALAM KECAMATAN SALIMPAUNG KABUPATEN TANAH DATAR - Arif Hidayat dan MHD Natsir (Universitas Negeri Padang, 2015)
This research was background by the success of PKBM As-Salam inimplementing learning activities of sewing course, this can be seen fromthe alumni who have opened their own businesses The aims of thisresearch to describe the Sewing Lessons in PKBM As-Salam at Districtof Tanah Datar Salimpaung, seen from the aspect of learning objectives,learning materials, learning methods, learning resources and learningevaluation. This research includes a quantitative descriptive research.The research use census method. Based on the results of research anddiscussion above, the learning implementation sewing activities runningsmoothly. The results of data processing shown that the implementationof learning in all aspects of sewing course covers the objectives,materials, methods, resources and evaluation of learning categorizedeither. It is suggested from the results of this study to the learningresources in order to further enhance the quality and quantity in theimplementation of learning.